Pengaruh corporate governance perception index dan kinerja keuangan terhadap nilai perusahaan - Suci Ramadhani (Pelantar Press, 2021)
The aim of this study examine the effect of corporate governance perception index and financial performance on corporate value. The study is based sample of companies the ranking corporate governance perception index (CGPI). As sample with 51 firm with purposive sampling. The analysis method regression analysis. The result indicate that corporate governance perception index has not significant influence to corporate value. This is because many corporate implemented corporate governance is only to follow government regulation. Financial performance has significant to corporate value. The higher financial performance, the higher the corporate value.